Formation of Fe3O4@SiO2@C/Ni hybrids with enhanced catalytic activity and histidine-rich protein separation. Issue 35 (19th August 2016) - Zhang, Yanwei; Zhang, Min; Yang, Jinbo; Ding, Lei; Zheng, Jing; Xu, Jingli; Xiong, Shenglin
Abstract : We have developed an extended Stöber method to construct Ni 2+ –Polydopamine (PDA) complex thin coating on Fe3 O4 @SiO2 spheres, which can be carbonized to produce the hybrid composites with metallic nickel nanoparticles embedded in PDA-derived thin graphitic carbon layer. Abstract : In this paper, we have developed an extended Stöber method to construct a Ni 2+ –polydopamine (PDA) complex thin coating on Fe3 O4 @SiO2 spheres, which can be carbonized to produce hybrid composites with metallic nickel nanoparticles embedded in a PDA-derived thin graphitic carbon layer (named Fe3 O4 @SiO2 @C/Ni). Interestingly, by introducing a thin SiO2 spacer layer between PDA–Ni 2+ and Fe3 O4, the reverse electron transfer from PDA to Fe3 O4 is probably able to be suppressed in the calcination process, which leads to the in situ reduction of only Ni 2+ by PDA instead of Fe3 O4 and Ni 2+ . Consequently, the size and density of nickel nanoparticles on the surface of SiO2 @Fe3 O4 can be finely adjusted. Moreover, it is found that the ability of tuning nickel nanoparticles is mainly dependent on the thickness of the spacer layer. When the thickness of the SiO2 spacer is beyond the electron penetration depth, the size and density of nickel nanoparticles can be exactly tuned. The as-prepared Fe3 O4 @SiO2 @C/Ni was employed as the catalyst to investigate the catalytic performance in the reduction of 4-nitrophenol (4-NP); furthermore, nickel nanoparticles decorated on Fe3 O4 @SiO2 @C spheres display a strong affinity to His-tagged proteins (BHb and BSA) via a specific metal affinity force between polyhistidine groups and nickel nanoparticles.